Ảnh hưởng đồng thời của cacbon hữu cơ hòa tan, chất hoạt động bề mặt và natri oxalat đến sự giải hấp thuốc trừ sâu - Hà, Trịnh Thu; W. Strowble, Bjarne; Trung, Nguyễn Quang; Giang, Lê Trường (Vietnam Journal of Chemistry, 2017)
This study investigated the effect of dissolved organic carbon (DOC), sodium dodecyl sulfate (SDS) and sodium oxalate (OXa) on desorption of endosulfan and dichlorodiphenyltrichloroethane (DDT) from soil in to water. The individual and interaction effects of three control parameters (DOC, SDS and OXa) on concentration of pesticides desorption was estimated by central composite rotatable design. Quadratic regression equations of response function (pesticides desorption) and variables were estimated. Statistical significant of models were confirm by square regression coefficient R2 which are 0.976 and 0.984 for endosulfan and DDT, respectively, adjusted square regression coefficient (R2adj) are 0.952 và 0.972 for endosulfan and DDT, respectively, it indicated that model fit to experiment data. Effects of independent variables DOC, SDS and Oxa on regression desorption concentrations pesticides were linear throughout regression coefficients at linear. Keywords. Response surface methodology, modeling, fenobucarb, dissolve organic carbon, surfactant.